Effect of ultrasound-guided serratus anterior plane block in pediatric patients undergoing pectus bar removal: a retrospective study of selected cases - Wu, Lianzhe; Xu, Zenghua; Zhang, Xuemei; Wang, Fang (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the effect of ultrasound-guided bilateral serratus anterior plane block (SAPB) in selected pediatric patients undergoing pectus bar removal, focusing on those with anticipated higher pain sensitivity or risk of opioid-related complications.MethodsA retrospective analysis was conducted on pediatric patients aged 6–17 years who underwent elective pectus bar removal under general anesthesia between September 2024 and February 2025. Patients were categorized into two groups: those receiving ultrasound-guided bilateral SAPB (Group S, n = 30) based on clinical factors such as pain sensitivity or risk of opioid-related complications, and a control group without SAPB (Group C, n = 46). Pain scores at rest and during coughing were assessed using the Numerical Rating Scale (NRS) immediately after awakening (Aldrete score ≥ 9) and at 1, 3, 6, 12, and 24 hours postoperatively. General patient information, dosages of sufentanil, propofol, and remifentanil, postoperative fentanyl supplementation, surgical duration, anesthesia duration, extubation time, and adverse events such as postoperative nausea and vomiting were recorded.ResultsGroup S exhibited significantly lower incidences of postoperative hypoxemia and lower resting and coughing NRS scores within 6 hours postoperatively compared to Group C (P < 0.008, Bonferroni-corrected). SAPB significantly reduced perioperative opioid use (P < 0.05). No statistically significant differences were observed in postoperative nausea and vomiting, delayed ambulation, or delayed oral intake (P > 0.05).ConclusionIn selected pediatric patients undergoing pectus bar removal, SAPB, as part of a multimodal analgesia regimen, was associated with improved perioperative analgesia, reduced postoperative hypoxemia, and decreased opioid use. While SAPB provides clear benefits in reducing postoperative pain and opioid use, we do not suggest routine implementation in all patients. Instead, its use should be individualized based on patient-specific factors such as pain sensitivity, previous analgesic response, and risk of opioid-related complications.